Electrodiagnostic Tests as Potential Efficacy Endpoints in Clinical Trials of Novel Pharmacological Therapies for Acquired Retinal Disorders - Magella M. Neveu; Victor Chong; Theo Empeslidis; Hendrik P.N. Scholl; Anthony G. Robson (Ophthalmic Research)
Background: Electrodiagnostic tests (EDTs) provide non-invasive, objective, and measurable indications of retinal and visual pathway function. These hold the promise of evaluating drug efficacy and disease progression over shorter periods than traditional “end-stage” outcome measures (e.g., best-corrected visual acuity) in various ophthalmological pathologies. The International Society for Clinical Electrophysiology of Vision has defined rigorous standards for EDTs, intended to optimize diagnostic power, enabling meaningful inter-laboratory comparisons and facilitating application as outcome measures in increasing numbers of multicentre clinical trials. Summary: This review outlines the main EDTs, including full-field, pattern, and multifocal electroretinography; the electro-oculogram; and the cortical visual-evoked potential, and highlights the possible role for monitoring disease progression and assessing treatment safety and efficacy. The utility and potential of EDTs are highlighted in studies that have assessed function and tested or monitored treatment safety or efficacy for a range of acquired retinal and optic nerve disorders, including central retinal vein occlusion, diabetic retinopathy, glaucoma, age-related macular degeneration, posterior uveitis, and autoimmune-related retinopathies. Key Messages: EDTs are fundamental to the diagnosis and phenotyping of many acquired retinal and visual pathway disorders. They also provide methods for the objective assessment of the efficacy and safety of potential novel treatments across short periods. Conventional psychophysical tests, such as visual acuity, are of limited value in localizing and characterizing dysfunction and are not always suitable for monitoring purposes. This review highlights where EDTs may address the need for better outcome measures to evaluate novel treatments within clinical trials, helping to select early treatment candidates and for the assessment of safety and efficacy.